High biodiesel yield from wet microalgae paste via in-situ transesterification: Effect of reaction parameters towards the selectivity of fatty acid esters. (15th July 2020) - Nguyen, Thanh Tien; Lam, Man Kee; Uemura, Yoshimitsu; Mansor, Nurlidia; Lim, Jun Wei; Show, Pau Loke; Tan, Inn Shi; Lim, Steven
Graphical abstract: Highlights: High biodiesel yield was produced from wet microalgae biomass. Moisture inhibition was contributed by reverse reaction due to the present of water. Increased methanol concentration and adding co-solvent can reduce moisture inhibition. n -Butanol and tetrahydrofuran had opposite selectivity towards fatty acid esters. Abstract: In the present study, the effect of co-solvent and different reaction parameters on fatty acid ester yield composition produced from in-situ transesterification of wet Chlorella vulgaris was investigated. The result showed that under wet microalgae condition (75 wt% of moisture content), increasing of methanol concentration resulted in more significant improvement of fatty acid ester yield as compared to H2 SO4 concentration. This was due to the equilibrium shifting to the FAME product direction under high methanol concentration condition. The highest fatty acid ester yield attained under wet microalgae condition was 96.0 wt% of esterifiable lipid with 650 mol/mol and 10000 mol/mol of H2 SO4 and methanol concentration, respectively. Besides, by introducing small amount of n -butanol or tetrahydrofuran (THF) (0.1 mol/mol of methanol) as co-solvent resulted to remarkable enhancement in fatty acid ester yield (100 wt% and 98.7 wt% of esterifiable lipid corresponding to n -butanol and THF, respectively) and 33% reduction of methanol usage. This was due to the synergetic effect of co-solvent in the lipid extraction process and enhancement of solubility between lipid and methanol phase to accelerate the transesterification reaction. Moreover, n -butanol or THF also lead to different selectivity of fatty acid esters, whereby high concentration of long-chain fatty acid esters (e.g. C18) were attained with n -butanol while short-chain fatty acid esters (e.g. C10 and C16) were obtained by adding THF. Overall, the results from the present study revealed the possibility to obtain high fatty acid ester yield from wet microalgae paste that could be useful for scale-up study.